(untitled) (Journal of the Spanish Institute for Strategic Studies, 2018)
International military forces have maintained a continuous presence in Afghanistan since 2001. Led by the United States through the Combined Security Transition Command–Afghanistan (CSTC-A), and together with the NATO Training Mission-Afghanistan (NTM-A), these international military forces created the Afghan National Security Forces (ANSF) we see today. The Forces are now indeed cohesive and are capable of stopping insurgency and providing both stability and security, as was shown during the presidential elections in April and June. But they also have very serious deficits which will need to be resolved over the coming years. Three major events will take place at the end of 2014: ISAF will finalise their activities, NATO will start its Resolute Support mission, and the ANSF will take over complete responsibility for the security of the country, with less and less support from the international community. The time is now ripe, therefore, to analyse the successes and failures of the implementation of the SSR technical model in the ANSF and, more specifically, in the Afghan National Army (ANA), and to look at the challenges they will face during the so-called Transformation Decade (2015-2024)